"Is Rational Choice Theory a Rational Choice of Theory?": (J. S. Coleman -T. J. Fararo (eds.) Rational Choice Theory: Advocacy and Critique. Newbury Park: Sage Publications, 1992.) - Schleicher, Nóra (Szociológiai Szemle, 2024)
-